Henryk Sienkiewicz w programach i podręcznikach dla szkół średnich przed rokiem 1918 = Henryk Sienkiewicz in school programmes and school literature for secondary schools in Poland before 1918 - Kulka, Bronisława (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The political situation in Poland was very difficult after the January Revolt (1863) and it was the reason that the nation was in need to have a writer who would lead their souls, who would point out the ideas, the ways of living after the time of the romantic writers.
Keywords: Sienkiewicz, Henryk (1846-1916) - twórczość; programy nauczania; podręczniki; szkolnictwo ponadpodstawowe; 19-20 w.